Curcumenol from Curcuma zedoaria: A second monoclinic modification - Hamdi, O.A.A.; Awang, K.; Hadi, A.H.A.; Syamsir, D.R.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, systematic name 9-isopropylidene-2,6dimethyl-11-oxatricyclo[6.2.1.0(1,5)] undec-6-en-8-ol, (CHO2)-H-15-O-22, which crystallizes with two molecules of similar conformation in the asymmetric unit, features three fused rings, two of which are five-membered and the third six-membered. Of the two five-membered rings, the one with an O atom has a distinct envelope shape(with the O atom representing the flap). The six-membered ring is also envelope-shaped as it shares a common O atom with the five-membered ring. In the crystal, the two independent molecules are linked by a pair of O-H center dot center dot center dot O hydrogen bonds, generating a dimer.